2011
DOI: 10.1111/j.1360-0443.2011.03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the impact of families on alcohol use: a lagged longitudinal study of early adolescents

Abstract: From the pre-teen to the mid-teen years, rates of alcohol use and misuse increase rapidly. Cross-sectional research shows that positive family emotional climate (low conflict, high closeness) is protective, and there is emerging evidence that these protective mechanisms are different for girls versus boys. Aims To explore gender differences in the longitudinal impact of family emotional climate on adolescent alcohol use and exposure to peer drinking networks. Design Three-wave two-level (individual, within-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
95
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 34 publications
9
95
0
4
Order By: Relevance
“…Studies that have assessed longitudinal patterns of underage alcohol use have examined time frames as short as 1 or 2 years (e.g., D'Amico et al, 2001;van den Eijnden et al, 2011;van der Vorst et al, 2006van der Vorst et al, , 2009 up to several years (e.g., Barnes et al, 2006;Danielsson et al, 2010;Duan et al, 2009;Hussong et al, 2008;Kelly et al, 2011;King et al, 2011;Martino et al, 2009;White et al, 2011). For example, this work has found that middle-schoolers' problems with selfcontrol predict high levels of alcohol use from Grade 8 to 11 (King et al, 2011), and low parental monitoring and high peer deviance in adolescence may be associated with higher initial levels and steeper increases of alcohol use across time (Barnes et al, 2006).…”
Section: U Nderage Alcohol Use Is Common In the United Statesmentioning
confidence: 99%
“…Studies that have assessed longitudinal patterns of underage alcohol use have examined time frames as short as 1 or 2 years (e.g., D'Amico et al, 2001;van den Eijnden et al, 2011;van der Vorst et al, 2006van der Vorst et al, , 2009 up to several years (e.g., Barnes et al, 2006;Danielsson et al, 2010;Duan et al, 2009;Hussong et al, 2008;Kelly et al, 2011;King et al, 2011;Martino et al, 2009;White et al, 2011). For example, this work has found that middle-schoolers' problems with selfcontrol predict high levels of alcohol use from Grade 8 to 11 (King et al, 2011), and low parental monitoring and high peer deviance in adolescence may be associated with higher initial levels and steeper increases of alcohol use across time (Barnes et al, 2006).…”
Section: U Nderage Alcohol Use Is Common In the United Statesmentioning
confidence: 99%
“…In their study of adolescents ages 10-16 years at Wave 1 through ages 16-22 years at Wave 3, Skeer et al (2011) found that family confl ict predicted an increased risk of substance use disorder. Finally, based on a sample of 10-year-olds followed through to 16 years of age (n = 854), Kelly et al (2011a) found that preceding family confl ict predicted alcohol consumption in girls.…”
mentioning
confidence: 99%
“…The study is unique because of its focus on a compressed developmental period that is clearly linked to the heightened impact of family factors (Nash et al, 2005), the growth of depressed mood for girls in particular (Garber et al, 2002;Mason et al, 2007;Saraceno et al, 2012), and the growth in heavy alcohol use that commonly occurs over this developmental period (Kelly et al, 2011a). The key hypotheses of the present study were that (a) family confl ict at Wave 1 (modal age 12 years for this study) would longitudinally predict depressed mood more strongly for girls relative to boys (Wave 2, modal age 13 years), and (b) depressed mood at Wave 2 would predict heavy alcohol use at Wave 3 (modal age 14 years).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that the quality of the relationship, rather than specific parenting practices, is important, as has been found in some studies (162,171,290).…”
Section: Descriptive Findingsmentioning
confidence: 93%